Study on the preparation of polymer-grafted coir fibre based adsorbent and its application to remove a reactive dye from aqueous solution - Ray, SK; Saha, P; Nur, HP; Saha, D; Hoque, AI; Saha, S (Bangladesh Journal of Scientific and Industrial Research, 2014)
Holocellulose was separated from Coir fibre by Sodium chlorite bleaching procedure. The adsorbent was synthesized by graft-copolymerization of acrylamide onto separated cellulose using potassium persulfate as a free radical initiator. Grafting percentage and grafting efficiency were measured and found to be 74.5 and 58% respectively. Prepared adsorbent was characterized by applying Fourier Transform- Infrared Spectrophotometer, Thermogravimetric/Differential Thermal Analyzer and Scanning Electron Microscope. Adsorbent prepared from holocellulose was successfully used at different adsorbent dosage, contact time, initial dye concentration and temperature to remove "Reactive Orange-16", a reactive dye from aqueous solution. Ultraviolet-Visible Spectrophotometric measurement of the dye in untreated and treated solutions showed that 0.2 g Holocellulose and Polyacrylamide-grafted holocellulose can remove 42% and 72% of Reactive Orange-16 dye from its 10 ppm aqueous solution within 1 hrs respectively. It may be proposed that Polyacrylamide-grafted holocellulose can be used in a traditional Textile Effluent Treatment Plant (ETP) as a cost effective adsorbent/alternative for decreasing the concentration of the reactive dye in the effluent. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.18277 Bangladesh J. Sci. Ind. Res. 48(4), 271-280, 2013